Foreign Direct Investments Of Gulf Sovereign Funds In Light Of The Effects Of Recent Crises -a Study Of The Russian-ukrainian Crisis And The Covid-19 Crisis- - Slimani Abdelkrim; Moghad Lakhdar (جامعة الوادي University Of Eloued, 2024)
This study aims to highlight the effects of the Russian-Ukrainian crisis and the Covid-19 crisis on the direct investments of Gulf sovereign funds, especially since the latter has been seeking for years to achieve economic diversification and contribute to the development of the economies of the Gulf countries. The study concluded that the most important impact on Gulf funds lies in the decline On the one hand, its funding sources and the increase in withdrawals to cover the increasing expenses of the countries that own it
Keywords: Gulf Sovereign Funds; Russian-Ukrainian crisis; Covid-19; Foreign Direct Investment; Economic diversification